Toughening of bone cement using nanoparticle: The effect of solvent - Misra N.; Kapusetti G.; Jaiswal S.; Maiti P. (My University, 2025)
Drawbacks of poly(methyl methacrylate) (PMMA)-based bone cement as a grouting agent for in vivo fixation of orthopedic and dental implants such as considerable low mechanical strength have been improved using nanotechnology. Bone cement-layered silicate nanocomposites have been prepared without any heat treatment in the presence of polar (dimethyl formamide, DMF) and nonpolar (benzene) solvents. Solvents have been removed completely from the bone cement after its preparation. Nanostructure is very much dependent on the solvent used for nanocomposite preparation, and benzene-based nanocomposites are highly intercalated, whereas DMF-based nanocomposites do not exhibit intercalation. Thermal stability of bone cement has improved in the presence of nanoclays. The relative enhanced interaction in case of benzene-based nanocomposites has been shown through FTIR and UV-vis studies. The significant improvement in modulus and toughness of bone cement has been demonstrated in the presence of minimum amount of nanoclay for benzene-based nanocomposites, whereas no change in modulus and reduced toughness have been observed for DMF-based nanocomposites. The decrease of contact angle has been witnessed with increasing nanoclay concentration indicating better hydrophilic materials suitable for biomedical applications for greater cell growth. The reason for varying property enhancement in different solvents has been discussed considering the polarity effect and interactions. © 2011 Wiley Periodicals, Inc.